The Communication Strategy Used by English Teachers in Teaching and Learning Process at Junior High School Number 17 Jambi City - Dira Evitarani; Yanti Ismiyati; Nurul Fitri (JELT: Journal of English Language Teaching, 2022)
The purpose of this study was to determine the types of communication strategies used by English teachers in the teaching and learning process and to explain the reasons for using these strategies at Junior High School Number 17 Jambi City in the 2021/2022 academic year. This study used qualitative research and data analysis was carried out by classroom observations and interviews with English teachers. The subjects of this study were four English teachers at Junior High School Number 17 Jambi City, using total sampling. The results of this study indicate that there are two approach communication strategies used by teachers in the teaching and learning process of English, namely two-way communication is the most widely used strategy by teachers in the classroom and one teacher uses two-way communication and also transactional communication in the learning process. learn to teach it. Thus, from the results of observations and interviews, this research concluded that teachers often use various communication strategies in the teaching and learning process of English so that students understand the lesson more easily.